The behavioral effects of frequent nightmares on stress tolerance - Hochard, Kevin D.; Heym, Nadja; Townsend, Ellen (American Psychological Association, 2016)
Frequent nightmares have been linked to daily distress using self-report measures. The present study investigated the impact of frequent nightmares on a stressful cognitive test requiring participants to perform additions of 2 previously displayed single digit numbers from a number series, where display latency between digits becomes increasingly short—the Paced Visual Serial Addition Task-Computerized (PVSAT-C). Participants experiencing frequent nightmares (n = 43) and controls (n = 42) were compared on PVSAT-C performance. A significant main effect of nightmare frequency was observed with participants in the frequent nightmare group enduring the task for a shorter duration than controls (a behavioral measure of stress tolerance). Results suggest that individuals experiencing frequent nightmares have a reduced tolerance for stressors, leading to increased daily vulnerability to stressful stimuli. This study confirms previous findings linking nightmares and daily distress and extends the literature by providing objective evidence for the link between nightmares and reduced stress tolerance through behavioral testing. These findings highlight nightmares as a salient target for clinical intervention.